PENGARUH KINERJA LINGKUNGAN TERHADAP LUAS PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DIMODERASI OLEH DEBT TO EQUITY RATIO (DER) (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di BEI 2011,2012, dan 2013) - Endah Yola Devita; Kirmizi -; Enni Savitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this study is to determine whether there is impact of environmental performance and Debt to Equity Ratio (DER) as variable moderating on Corporate Social Responsibility Disclosure. The population of this study is manufactued companies listing in Indonesian Stock Excchange  for the periode 2011 to2013  and this study uses a sample of 85 companies which are registered as PROPER and publish their annual report. This study uses regression analysis to be treated with the program SPSS for Windows 18. The results show that the impact of environmental performance toward CSR disclosure is significant and DER as a moderating variable in its interaction with environmental performance has significant impact toward CSR disclosure. Keywords: CSRD, DER, Environmental, and Performance